Transactions with the World Ecocriticism and the Environmental Sensibility of New Hollywood - O'Brien, Adam (Berghahn Books, 2016)
In their bold experimentation and bracing engagement with culture and politics, the "New Hollywood" films of the late 1960s and early 1970s are justly celebrated contributions to American cinematic history. Relatively unexplored, however, has been the profound environmental sensibility that characterized movies such as The Wild Bunch, Chinatown, and Nashville. This brisk and engaging study explores how many hallmarks of New Hollywood filmmaking, such as the increased reliance on location shooting and the rejection of American self-mythologizing, made the era such a vividly "grounded" cinematic moment. Synthesizing a range of narrative, aesthetic, and ecocritical theories, it offers a genuinely fresh perspective on one of the most studied periods in film history.